Regenerating Places outside the Metropolis. A Reading of Three Global Art-Related Processes and Development Trajectories - Ludovico Centis (MDPI AG, 2021)
The aim of the paper is to reflect on the intersection of two relevant phenomena that unfolded in recent decades in all the most industrialized countries and economies—from the United States to Europe and Japan—as the shrinkage of vast urban and rural areas and the increasing role of culture as a driver for economic growth and social development. The attention is focused on the role of art as one of the main engines of territorial regeneration. Three case studies—Verzegnis in Italy, the Seto Islands in Japan, Marfa in the United States—have been selected to open a reflection on the relation between culture, art and regeneration on a global scale. To measure these effects, the research intertwined field explorations, access to primary and secondary texts, an original mapping of the sites and a series of targeted interviews through an extensive questionnaire. The research addresses the role played by art and culture both in the reuse of abandoned buildings and spaces and in the activation, involvement and self-empowerment of the inhabitants. The aim is not the definition of an immediately generalizable model but to reach the first synthesis, identifying general characters and opening future research paths that engage with the theoretical and practical implementation of politics related to heritage, culture and innovative regeneration processes.